A new etiology for variant of Guillain-Barré syndrome: bariatric surgery - Şahin, Şevki; Ateş, Miruna Florentina; Çınar, Nilgün; Karşıdağ, Sibel (The European Research Journal, 2019)
Bariatric surgery is an effective treatment for obesity. However, the number of acute or chronic neurological complications after bariatric surgery, including Guillain-Barré syndrome, is increasingly reported. We present here two cases which developed acute motor sensory polyneuropathy a couple months after bariatric surgery which rapidly progressed over the following month. Both patients used received parenteral vitamin B complex replacement after surgery. The first case responded well to intravenous immunoglobulin (IVIg) treatment. However, the second case required plasmapheresis and physical rehabilitation for recovery after IVIg treatment. It is thought that minerals, vitamins, and trace element deficiencies can develop after bariatric surgery. These deficiencies may trigger inflammatory and autoimmune mechanisms and cause acute polyneuropathies. In such cases, it should be kept in mind that immune therapies may be beneficial, as well as vitamins.